1996
DOI: 10.1016/s0969-2126(96)00150-5
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a fungal elicitor secreted by Phytophthora cryptogea, a member of a novel class of plant necrotic proteins

Abstract: The determination of the crystal structure of a member of the elicitin family may make it possible to separate the activity that causes leaf necrosis from that inducing systemic acquired resistance to pathogens, making it feasible to engineer a non-toxic elicitin that only elicits plant defences. Such studies should aid the development of non-toxic agricultural pest control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 46 publications
0
74
0
2
Order By: Relevance
“…The close correlation found between replacement efficiency and affinity for sterols ( Figure 2B) strongly suggests that cryptogein displacement from its binding sites is secured only by sterol-loaded elicitins. The purified proteins (native state) from both Phytophthora and Pichia culture filtrates are "void," i.e., sterol-unloaded proteins, as it appeared in this work and from structural (Boissy et al, 1996;Fefeu et al, 1997;Gooley et al, 1998) and chemical (Mikes et al, 1997(Mikes et al, , 1998 analyses. It was previously reported that elicitins easily bind sterols from tobacco plasma membranes (Vauthrin et al, 1999).…”
Section: Role Of Sterol-elicitin Complexes In Elicitin Binding To Spementioning
confidence: 52%
See 4 more Smart Citations
“…The close correlation found between replacement efficiency and affinity for sterols ( Figure 2B) strongly suggests that cryptogein displacement from its binding sites is secured only by sterol-loaded elicitins. The purified proteins (native state) from both Phytophthora and Pichia culture filtrates are "void," i.e., sterol-unloaded proteins, as it appeared in this work and from structural (Boissy et al, 1996;Fefeu et al, 1997;Gooley et al, 1998) and chemical (Mikes et al, 1997(Mikes et al, , 1998 analyses. It was previously reported that elicitins easily bind sterols from tobacco plasma membranes (Vauthrin et al, 1999).…”
Section: Role Of Sterol-elicitin Complexes In Elicitin Binding To Spementioning
confidence: 52%
“…They are buried inside the core in a highly hydrophobic environment; therefore, Y-F exchange (almost similar steric hindrance but higher hydrophobicity) results in minor changes in the aromatic ring orientations. This was partially demonstrated by circular dichroism, chromatographic, electrophoretic, and spectrophotometric properties (Osman, Vauthrin, Mikes, Milat, Panabières, Marais, Brunie, Maume, Ponchet, and Blein, unpublished results) and was confirmed by the modeling of these mutations in the Swiss-PdbViewer program, with the use of a crystal structure (pdb 1beo; Boissy et al, 1996) and 18 solution structures (pdb 1beg; Fefeu et al, 1997). In fact, the Y-F replacements, after energy minimization, led to small changes in the ring orientation, close to the average position of tyrosine residues revealed by the solution structures.…”
Section: Cryptogein and Mutated Elicitin Characteristicsmentioning
confidence: 78%
See 3 more Smart Citations